Framework for evaluating efficacy in Health Promoting Schools. Issue 3 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – Successful implementation of Health Promoting Schools (HPS) depends on putting the model in the schools' context for both health improvement and school improvement. HPS can only be effective if the change can be sustained over an extended duration. The purpose of this paper is to discuss development of the HPS process by University Research Centre in Hong Kong, resulting in an award scheme, where no additional resources were initially provided by the authorities.Design/methodology/approach – The team adopted a step‐by‐step approach starting with capacity building of key stakeholders and comprehensive needs assessment, leading to development of a system of evaluation and monitoring and establishment of a "Healthy School Award" system. The system was built on data derived from several different sources and made use of qualitative and quantitative information and were intended to be used to guide practice and actions for improvement.Findings – Schools measured their own performance against established school and student health profiles. The validated system of evaluation and monitoring led to a Healthy School Award scheme for participating schools with "accredited" and "award" designations. The award system evaluated six key HPS areas and identified exemplars of HPS as resource schools to form a strong network.Research limitations/implications – HPS can be regarded as new paradigm of schooling rather than an add‐on programme.Practical implications – HPS can be regarded as new paradigm of schooling rather than an add‐on programme. The advantage of an academic institution masterminding the development process lies with their strength in education and research, building on the professionalism of school educators in health promotion and developing evidence‐based HPS practice.Originality/value – This paper discusses an approach for addressing the key factors associated with initiation of innovation and management of change in an education setting. The involvement of both higher education and an award scheme can act strong catalysts to drive change, resulting in a strong evidence base with and results demonstrating effectiveness, which then led to government support. Acknowledgements : The authors gratefully acknowledge funding support for the Quality Education Fund of Hong Kong Special Administrative Region Government and the schools participated in the Healthy School project throughout the years.